Functional Analyses of Complement Convertases Using C3 and C5-Depleted Sera - Okroj, Marcin; Holmquist, Emelie; King, Ben C.; Blom, Anna M. (PLOS ONE, 2012)
C3 and C5 convertases are central stages of the complement cascade since they converge the different initiation pathways, augment complement activation by an amplification loop and lead to a common terminal pathway resulting in the formation of the membrane attack complex. Several complement inhibitors attenuate convertase formation and/or accelerate dissociation of convertase complexes. Functional assays used to study these processes are often performed using purified complement components, from which enzymatic complexes are reconstituted on the surface of erythrocytes or artificial matrices. This strategy enables identification of individual interactions between convertase components and putative regulators but carries an inherent risk of detecting non-physiological interactions that would not occur in a milieu of whole serum. Here we describe a novel, alternative method based on C3 or C5-depleted sera, which support activation of the complement cascade up to the desired stages of convertases. This approach allows fast and simple assessment of the influence of putative regulators on convertase formation and stability. As an example of practical utility of the assay, we performed studies on thioredoxin-1 in order to clarify the mechanism of its influence on complement convertases.